Does the SOFA Score Have the Ability to Predict Length of Stay and Mortality as well as Other Scorings? - Adhiputri, Artrien; Hapsari, Brigitta Devi Anindita; Reviono, Reviono; Alfarizi, Aditya; Damayanti, Raninditya (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: In the intensive care unit (ICU), critically sick pneumonia has a high mortality rate, so forecasting the prognosis is crucial for making decisions. Early detection of clinical deterioration and the implementation of early intervention and care can be achieved through the use of scoring systems. The Acute Physiology and Chronic Health Evaluation II (APACHE II) scoring system is a better system in predicting mortality in critically ill patients. However, in this study, we aim to observed the use of the Sequential Organ Failure Assessment (SOFA) score as a predictor of mortality and length of stay (LOS). Methods: From April to August 2023, we treated 125 critically sick pneumonia patients in the ICU as part of a prospective observational research. An integrated ICU mortality calculator was used to assess the performance of the APACHE II, Simplified Acute Physiology Score II (SAPS II), and SOFA scores. Descriptive statistics will be used for data analysis, and the Fisher exact test and Chi-square test will be used for testing. logistic regression and linear regression methods are used in multivariate analysis. If the p-value is less than 0.05, it will be statistically significant. Results: APACHE II, SAPS II, and SOFA scores were significant in predicting the outcome of critically ill pneumonia patients (cut-off of ≥14.5, ≥34.5, and ≥3.5, respectively). The Spearman rank correlation for LOS shows that APACHE II, SOFA, and SAPS II scores have a very weak relationship with the p-values are 0.121, 0.766, and 0.436, respectively. Conclusion: The SOFA score is a good mortality predictor in critically ill pneumonia patients yet is simpler and easier to use in all settings in the hospital.